2014
DOI: 10.1007/s00062-014-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome: The Spectrum of MR Imaging Patterns

Abstract: The spectrum of imaging findings in PRES is wide. Almost always subcortical and cortical structures are involved. Although posterior changes are prominent in this syndrome, frontal involvement is more frequent than posterior on FLAIR imaging and DWI. On DWI, mixed patterns are not uncommon. Reversibility generally takes place independent of DWI pathology. Hypertension was not a prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 33 publications
6
43
0
11
Order By: Relevance
“…Kastrup et al reported that the frontal region was the area most commonly affected in a study of PRES cases. 15 The MRI brain scans of the two patients in the current report confirm this, as the frontal region was involved in both cases. Reversibility of MRI findings is suggestive of a good prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…Kastrup et al reported that the frontal region was the area most commonly affected in a study of PRES cases. 15 The MRI brain scans of the two patients in the current report confirm this, as the frontal region was involved in both cases. Reversibility of MRI findings is suggestive of a good prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…Gyral and leptomeningeal enhancement was previously reported, and this was interpreted as leakage due to direct endothelial injury causing blood-brain barrier breakdown (12,13). Hefzy and his colleagues previously described three distinct types of hemorrhage, including focal minute hemorrhages, larger more typical focal hematomas, and sulcal-based subarachnoid hemorrhage (14).…”
Section: Discussionmentioning
confidence: 97%
“…It classically occurs in the cortical or subcortical regions of the dominant parieto-occipital lobes, holohemispheric watershed zones, superior frontal sulcal area, and, rarely, the brain stem or basal ganglia. 16,23,24 MR imaging typically demonstrates vasogenic edema in the subcortical white matter and cortex. Cytotoxic edema has been described in a relatively lower percentage of patients with posterior reversible encephalopathy syndrome.…”
Section: Discussionmentioning
confidence: 99%